2018
DOI: 10.1542/peds.2017-2790
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Teen Dating Violence Perpetration

Abstract: OBJECTIVES: With our study we aimed to (1) understand what factors uniquely conferred risk for physical and sexual forms of teen dating violence (TDV) perpetration and (2) create a screening algorithm to quantify perpetration risk on the basis of these factors. METHODS:A total of 1031 diverse public high school students living in Southeast Texas participated in our study (56% female; 29% African American, 28% white, and 31% Hispanic). Self-report measures concerning TDV and associated risk factors were complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 62 publications
(32 reference statements)
0
26
0
4
Order By: Relevance
“…In addition, it has been reported that 65% of women in Australia who have experienced DV had children in their care at the time of the abuse, and that these children had either seen or heard the violence as it was occurring (Australian Bureau of Statistics, 2017). Similar to the effects of trauma on child development, research on the impact of DV on children has found that DV is associated with greater risk of childhood mental illness (Sonego et al, 2018), problems engaging socially with peers (Vikse Nicholson et al, 2018), lowered academic achievement (Kiesel et al, 2016), and greater lifetime risk of DV exposure (Cohen et al, 2018). Enlow et al (2012) found that young children who had witnessed DV had lower intelligence scores when compared to children who had not experienced DV.…”
mentioning
confidence: 99%
“…In addition, it has been reported that 65% of women in Australia who have experienced DV had children in their care at the time of the abuse, and that these children had either seen or heard the violence as it was occurring (Australian Bureau of Statistics, 2017). Similar to the effects of trauma on child development, research on the impact of DV on children has found that DV is associated with greater risk of childhood mental illness (Sonego et al, 2018), problems engaging socially with peers (Vikse Nicholson et al, 2018), lowered academic achievement (Kiesel et al, 2016), and greater lifetime risk of DV exposure (Cohen et al, 2018). Enlow et al (2012) found that young children who had witnessed DV had lower intelligence scores when compared to children who had not experienced DV.…”
mentioning
confidence: 99%
“…Across the four levels of the social ecology described here, there has been the greatest amount of research on predictors of TDV at the individual level. Individual-level predictors of perpetration include prior aggressive and antisocial behaviors such as engaging in delinquency and bullying (Foshee et al 2014), holding attitudes accepting of traditional gender norms and condoning dating violence (Cohen et al 2018;Connolly et al 2010), anger and hostility (Vagi et al 2013), internalizing symptoms such as depression and anxiety, and substance use (Chen et al 2018). While internalizing symptoms like depression and anxiety predict TDV perpetration, the effect is found to be stronger among girls compared to boys (McCloskey and Lichter 2003).…”
Section: Risk Factors For Perpetrationmentioning
confidence: 99%
“…Certain factors within the family are important predictors of perpetrating TDV. A significant body of research demonstrates that exposure to violence and victimization in the home increases the risk of TDV (Chen et al 2018;Cohen et al 2018). This includes both being a direct victim of violence and witnessing violence in the home (such as domestic abuse between parents, or a parent abusing a sibling).…”
Section: Risk Factors For Perpetrationmentioning
confidence: 99%
“…Notwithstanding inconsistent estimates of the prevalence of dating violence among different groups of teens, the consequences associated with this experience are profound. A robust body of research documents numerous short-and long-term adverse physical, psychological, and academic outcomes (Chiodo et al, 2011;Cohen, Shorey, Menon, & Temple, 2018;Foshee, McNaughton Reyes, Gottfredson, Chang, & Ennett, 2013). For example, victims of teen dating violence have been found to experience multiple symptoms of anxiety and depression (Exner-Cortens, Eckenrode, & Rothman, 2013).…”
Section: Teen Involvement In Violent Dating Relationshipsmentioning
confidence: 99%